Takayasu Arteritis Affecting Only Renal Arteries: A Rare Cause of Renovascular Hypertension - britel, Driss; Bourzine, Nadia; Taous, Hamza; Benyass, Aatif (RA Journal of Applied Research, 2018)
Takayasu Arteritis (Ta) Is An Inflammatory Process Frequently Associated With Stenosis And Obliteration Of The Aorta And Its Primary Branches With Unknown Etiology. This Manifestation Can Lead To Renovascular Hypertension Then To Renal Failure. Renovascular Hypertension Is Generally Resistant To Medical Therapy And Often Requires Additional Invasive Management Strategies, Such As Angioplasty Or Surgical Bypass. We Will Present A Case Of 20-Year-Old Patient That Had Severe Hypertension Due To Takayasu Arteritis Affecting Only The Renal Arteries. Our Case Aims To Improve Awareness Of This Condition Among Clinicians Because Early Diagnosis And Treatment Are The Only Way To Avoid The Onset Of Serious Complications Of Hypertension And To Preserve Renal Function.